Environmental pediatric physiotherapy and risky play: making the case for a perfect match - Sturm, Andrea; Sandseter, Ellen Beate Hansen; Scheiber, Barbara (Frontiers in Public Health, 2025)
Environmental physiotherapy is epistemologically anchored in the critical recognition that physiotherapeutic practice is fundamentally embedded within a planetary ecological framework, demanding a holistic, systemically integrated approach to professional practice. This perspective article highlights and underscores the value of risky play for child health and the commonalities with environmental pediatric physiotherapy. The article starts with a discussion of current challenges in child health around the globe, often resulting from a lack of physical activity of children, and claims finding new, promising and sustainable ways that are able to attract children and their parents to playfully increase the time that children are physically active. Followed by an overview of physiotherapists’ roles and responsibilities in child public health, the authors point to the need to move beyond an isolated profession-centric approach when tackling the existing, concerning issues in child health worldwide. Foundational information about risky play underpinned with scientific results and its acknowledgment by other health professions is then presented. By including a perspective of what children want, the authors identify a gap between the world’s children’s actual needs and current societal offers. The benefits of risky play for child health are presented in detail, along with a discussion of various considerations pertaining to child safety. Concluding, this perspective article demonstrates how physiotherapists can contribute to better child health by including risky play in physiotherapy theory and practice.